Affective enactments: the pedagogy and cultural politics of reading in an Australian classroom. Issue 1 (2nd January 2023) - Purcell, Mary
ABSTRACT: This paper concerns the pedagogical work affect does in an Australian Year 11 literature classroom. Thinking with Ahmed's framing of affect from the viewpoint of cultural politics, I consider how affect aligns some bodies within particular social groups and situates some outside. Three key moments of affective charge are drawn from observations: students' written responses, group discussions, and interviews. Analysing these moments from the perspective of Ahmed's affective economy foregrounds the value of detecting students' orientations towards or away from the classroom space, discourses, and practices. It indicates the potential for constructing the classroom as an inclusive and relational space allowing room for the different knowledges implicit in students' experiences. It shows that students often find themselves interpellated by conflicting discourses that emphasise how they read themselves and their texts. Allowing opportunities to name, share, and process these conflicts can expand the efficacy of reading practices.